2021
DOI: 10.3390/buildings12010013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Predicting Energy Consumption of Absorption Heat Pump with Multilayer Shallow Neural Network Training Algorithms

Abstract: The performance of various multilayer neural network algorithms to predict the energy consumption of an absorption chiller in an air conditioning system under the same conditions was compared and evaluated in this study. Each prediction model was created using 12 representative multilayer shallow neural network algorithms. As training data, about a month of actual operation data during the heating period was used, and the predictive performance of 12 algorithms according to the training size was evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thus, homeowners can improve the energy performance of their homes and contribute to a more sustainable future. The value of reducing energy consumption in buildings has increased worldwide, so the adoption of energy efficiency techniques during the construction and operation of office and residential buildings would play an important role in the creation of sustainable cities in the future (Kim et al, 2022). Energy performance and efficiency in the home is a major concern for households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, homeowners can improve the energy performance of their homes and contribute to a more sustainable future. The value of reducing energy consumption in buildings has increased worldwide, so the adoption of energy efficiency techniques during the construction and operation of office and residential buildings would play an important role in the creation of sustainable cities in the future (Kim et al, 2022). Energy performance and efficiency in the home is a major concern for households.…”
Section: Discussionmentioning
confidence: 99%
“…Decent remuneration for apprenticeships and public funding of retraining schemes are important factors in attracting new users and citizens who implement technology. Governments can also play an important role in promoting training for heat pump installation to potentially induce a positive perception (Kim et al, 2022). Thus, we hypothesize the following:…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 97%
“…For the ANN model, the Neural Networks Toolbox of MATLAB (R2020a) was used to create a neural network. The NARX Feedforward Neural Networks model is a multi-layer perceptron ANN model that consists of an input layer, a hidden layer, and an output layer [26]. In addition, the Levenberg-Marquardt algorithm was used to find the minimum of a function over a space of parameters, which is a popular trust algorithm.…”
Section: Ann Modelmentioning
confidence: 99%
“…In addition, the Levenberg-Marquardt algorithm was used to find the minimum of a function over a space of parameters, which is a popular trust algorithm. A similar structure of the ANN model used in the previous studies was used for the present study, and the structure is shown in Figure 2 [26,27].…”
Section: Ann Modelmentioning
confidence: 99%